Integrated Correlation Analysis of Phytoplankton Community Structure and Physicochemical Parameters for Water Quality Assessment in Ranu Grati, Indonesia - Nayunda Bella Justicia; Punya Madee (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to analyze the relationship between phytoplankton abundance and physicochemical parameters in the waters of Ranu Grati and to evaluate the water quality status based on Government Regulation of the Republic of Indonesia Number 22 of 2021. Methodology: This study employed a descriptive quantitative method using field observation and laboratory analysis. Water samples were collected from several sampling stations in Ranu Grati. Physicochemical parameters were measured using a thermometer, Secchi disk, pH meter, DO meter, and spectrophotometer. Phytoplankton identification was conducted microscopically using an Olympus binocular microscope, while correlation analysis was performed using Microsoft Excel and SPSS software. Main Findings: A total of 18 phytoplankton genera belonging to six divisions were identified in the waters of Ranu Grati. Temperature, pH, dissolved oxygen, and total nitrogen met the Class III water quality standards, whereas transparency, BOD, COD, and total phosphate exceeded the permissible limits. Correlation analysis revealed that transparency, dissolved oxygen, BOD, COD, total nitrogen, and total phosphate strongly influenced phytoplankton abundance and distribution patterns. Novelty/Originality of this study: This study provides updated scientific information regarding the ecological relationship between phytoplankton communities and physicochemical parameters in Ranu Grati waters using correlation-based analysis integrated with national water quality standards. The findings contribute to the development of ecological monitoring data and provide a scientific basis for sustainable lake management and aquatic ecosystem conservation in tropical inland waters.